Identification of key genes and pathways in chronic rhinosinusitis with nasal polyps and asthma comorbidity using bioinformatics approaches - Wang, Mingming; Tang, Shuangmei; Yang, Xiaoqi; Xie, Xinyu; Luo, Yang; He, Shaojuan; Li, Xuezhong; Feng, Xin (Frontiers in Immunology, 2022)
Patients of Chronic rhinosinusitis with nasal polyps (CRSwNP) and asthma comorbidity (ACRSwNP) present severe symptoms and are more likely to relapse. However, the pathogenesis of ACRSwNP is not fully understood. This study aimed to explore the underlying pathogenesis of ACRSwNP using bioinformatics approaches. ACRSwNP-related differentially expressed genes (DEGs) were identified by analysis of GSE23552 and GSE104468 datasets. The clusterProfiler R package was used to carry out functional and pathway enrichment analysis. A protein-protein interaction (PPI) network was built using STRING database to explore key genes in pathogenesis of ACRSwNP. The bioinformatic analysis results were verified through qRT-PCR. Connectivity Map (CMap) database was used to predict potential drugs for treatment of ACRSwNP. A total of 36 DEGs were identified, which were mainly enriched in terms of regulation of immune response and detection sensory perception of taste. Thirteen hub genes including AZGP1, AQP9, GAPT, PIP and PRR4 were identified as potential hub genes in ACRSwNP from the PPI network. Analysis of the GSE104468 dataset showed that upregulation of CST1 and CST2 in nasal mucosa was associated with asthma. qRT-PCR detection confirmed the bioinformatic analysis results. Tacrolimus and spaglumic acid were identified as potential drugs for treatment of ACRSwNP from CMap database. The findings of this study provide insights into the pathogenesis of ACRSwNP and may provide a basis for discovery of effective therapeutic modalities for ACRSwNP.